2002
DOI: 10.1111/j.1469-445x.2002.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony analysis between blood pressure and sympathetic nerve signal inhibited by atrial receptor stimulation in Wistar rats

Abstract: Recently attempts have been made to analyse blood pressure (BPI and renal sympathetic nerve activity (RSNA) to determine how patterns contained within them might reflect control by the autonomic nervous system. TO date, these studies have primarily used coherence analysis of BP and RSNA in the frequency domain. However, this analysis is unable to assess the non-linear properties of the underlying cardiovascular control system. In t h i s study we employed not only coherence analysis but also cross-entropy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Thus, although the functional importance of the lack of synchrony remains to be established, the data suggest that the central brain circuits become more primed to defend the body against a decrease in blood volume. The opposite is likely to accompany an increase in blood volume, as we recently showed by applying the same non‐linear dynamic statistical method to a reduction in RSNA induced by stimulating cardiac atrial receptors (Yang et al 2002 b ).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, although the functional importance of the lack of synchrony remains to be established, the data suggest that the central brain circuits become more primed to defend the body against a decrease in blood volume. The opposite is likely to accompany an increase in blood volume, as we recently showed by applying the same non‐linear dynamic statistical method to a reduction in RSNA induced by stimulating cardiac atrial receptors (Yang et al 2002 b ).…”
Section: Discussionmentioning
confidence: 82%
“…In an attempt to address this issue, a number of investigations have applied mathematical methods to measure patterns of activity and one of the most developed approaches is power spectral analysis. Studies in experimental animals have revealed that, in the renal sympathetic nerve, major energy peaks occur at heart rate frequency, respiratory frequency and also at much lower frequencies (Persson et al, 1992;Malpas et al, 1998;Burgess et al, 1999;Yang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…XSampEnt also assesses the pattern synchronization between time series rather than just strict nontemporal (zero lag) cross-relation (Richman and Moorman, 2000;Xie et al, 2010). XSampEnt has been successfully applied to the analysis of cardiovascular measures (Yang et al, 2002), renal sympathetic nerve activity (Zhang et al, 2007), fMRI data (Hu and Shi, 2006), EEG data (Vakorin et al, 2010;Xie et al, 2010), and financial data (Liu et al, 2010).…”
mentioning
confidence: 99%